Review of surfactant-assisted chemical enhanced oil recovery for carbonate reservoirs: challenges and future perspectives - Sreela Pal; M. Mushtaq; Fawzi Banat; Ali M. Al Sumaiti (Petroleum Science, 2017)
Abstract A significant fraction of the conventional oil reserves globally is in carbonate formations which contain a substantial amount of residual oil. Since primary and secondary recovery methods fail to yield above 20%–40% of original oil in place from these reserves, the need for enhanced oil recovery (EOR) techniques for incremental oil recovery has become imperative. With the challenges presented by the highly heterogeneous carbonate rocks, evaluation of tertiary-stage recovery techniques including chemical EOR (cEOR) has been a high priority for researchers and oil producers. In this review, the latest developments in the surfactant-based cEOR techniques applied in carbonate formations are discussed, contemplating the future direction of existing methodologies. In connection with this, the characteristics of heterogeneous carbonate reservoirs are outlined. Detailed discussion on surfactant-led oil recovery mechanisms and related processes, such as wettability alteration, interfacial tension reduction, microemulsion phase behavior, surfactant adsorption and mitigation, and foams and their applications is presented. Laboratory experiments, as well as field study data obtained using several surfactants, are also included. This extensive discussion on the subject aims to help researchers and professionals in the field to understand the current situation and plan future enterprises accordingly.